O pasji naukowej i pożytkach z niej płynących - Chmielewska-Banaszak, Danuta (Warszawa: Zakład Narodowy im. Ossolińskich)
My paper is devoted to scientific passion and its connections with scientific effectiveness. Following some preliminary considerations concerning a context of my paper. I come to description of mechanisms determining a level of engagement into scientific activities.
Keywords: naukoznawstwo; psychologia twórczości